Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization

Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Insertion copolymerization of difunctional polar vinyl monomers with ethylene - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Chikkali, Samir H. (ACS Macro Letters, 2015)
A single-step synthesis, structural characterization and application of a neutral, acetonitrile ligated, palladium-phosphinesulfonate complex [{P<\^>O}PdMe(L)] (P<\^>O = K-2-P,O Ar2PC6H4SO2O with Ar = 2-MeOC6H4; L = CH3CN) (3) in coordination/insertion copolymerization of ethylene with difunctional olefin is investigated. In a significant development, complex 3 was found to catalyze insertion copolymerization of industrially relevant 1,1-disubstituted difunctional vinyl monomers for the first time. Thus, insertion copolymerization of ethyl-2-cyanoacrylate (ECA or super glue) and trifluoromethyl acrylic acid (TFMAA) with ethylene produced the corresponding copolymers with 6.5% ECA and 3% TFMAA incorporation. Increasing the concentration of difunctional olefins led to higher incorporation but at the expense of lower activities. These observations indicate that complex 3 tolerates difunctional vinyl monomers and provides direct access to difunctional polyolefins that have not been attempted before.

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis

Impact of modular substitution on crystal packing: the tale of two ureas - Koshti, Vijay S.; Thorat, Shridhar H.; Gote, Ravindra P.; Chikkali, Samir H.; Gonnade, Rajesh G. (CrystEngComm, 2016)

Intramolecular ipso-arylative cyclization of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts through merged gold/visible light photoredox catalysis - Bansode, Avinash H.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2017)
A visible-light-promoted merged gold/photoredox catalyzed ipsoarylative cyclization has been reported. For instance, the reaction of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts in the presence of catalytic amounts of [(4-OCH3)C6H4](3)PAuCl and Ru(bpy)(3)(PF6)(2) under irradiation using a 32WCFL bulb gave arylated spirocarbocycles in moderate to good yields.

Inositol to aromatics -benzene free synthesis of poly oxygenated aromatics - Gurale, Bharat P.; Shashidhar, Mysore S.; Sardessai, Richa S.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
A method for the preparation of benzene derivatives from myo-inositol, an abundantly available phyto chemical is described. 1,3-Bridged acetals of inososes undergo step-wise elimination leading to the formation of polyoxygenated benzene derivatives. This aromatization reaction proceeds through the intermediacy of a beta-alkoxyenone, which could be isolated. This sequence of reactions starting from myoinositol, provides a novel route for the preparation of polyoxygenated benzene derivatives including polyoxygenated biphenyl. This scheme of synthesis demonstrates the potential of myo-inositol as a sustainable non-petrochemical resource for aromatic compounds. (C) 2018 Elsevier Ltd. All rights reserved.

Influence of fluorine substitution on the molecular conformation of 3 `-deoxy-3 `-fluoro-5-methyluriaine - Aher, Manisha N.; Erande, Namrata D.; Kumar, Vaijayanti A.; Fernandes, Moneesha; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2020)
{Fluorine substitutions on the furanose ring of nucleosides are known to strongly influence the conformational properties of oligonucleotides. In order to assess the effect of fluorine on the conformation of 3'-deoxy-3'-fluoro-5-methyluridine (T-R(F)), C-10 H13FN2O5, we studied its stereochemistry in the crystalline state using X-ray crystallography. The compound crystallizes in the chiral orthorhombic space group P2(1)2(1)2(1) and contains two symmetry-independent molecules (A and B) in the asymmetric unit. The furanose ring in molecules A and B adopts conformations between envelope (E-2, 2'-endo
Keywords: crystal structure; fluoro nucleoside; pseudorotation parameter; sugar puckering; uridine

Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin

Intramolecular donor-stabilized tetra-coordinated germanium(iv) di-cations and their Lewis acidic properties - Peddi, Balakrishna; Khan, Souvik; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Chemical Science, 2023)
We report the first examples of intramolecular phosphine-stabilized tetra-coordinated germanium(iv) di-cationic compounds: [(L2Ge)-Ge-iPr][CF3SO3](2)3iPr and [(L2Ge)-Ge-Ph][CF3SO3](2)3Ph (L-iPr = 6-(diisopropylphosphanyl)-1,2-dihydroacenaphthylene-5-ide; L-Ph = 6-(diphenylphosphanyl)-1,2-dihydroacenaphthylene-5-ide). The step wise synthetic strategy involves the isolation of neutral and mono-cationic Ge(iv) precursors: [(L2GeCl)-Ge-iPr][X] (X = GeCl(3)1iPr, OTf 2iPr), [(L2GeCl2)-Ge-Ph] 1Ph and [(L2GeCl)-Ge-Ph][OTf] 2Ph. Both 3iPr and 3Ph exhibit constrained spiro-geometry. DFT studies reveal the dispersion of di-cationic charges over P-Ge-P sites. Anion or Lewis base binding occurs at the Ge site resulting in relaxed distorted trigonal bipyramidal/tetrahedral geometry. 3iPr and 3Ph activate the Si-H bond initially at the P-site. The hydride ultimately migrates to the Ge-site rapidly giving [(L2GeH)-Ge-Ph][CF3SO3] 3PhH, while sluggishly forming [(L2GeH)-Ge-iPr][CF3SO3] 3iPrH. Compounds 3iPr and 3Ph were tested as catalysts for the hydrosilylation of aromatic aldehydes. While catalytic hydrosilylation proceeded via the initial Et3Si-H bond activation in the case of 3iPr, compound 3Ph as a catalyst showed a masked Frustrated Lewis Pair (FLP) type reactivity in the catalytic cycle.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter